The soluble form of HFE protein regulates hephaestin mRNA expression in the duodenum through an endocytosis-dependent mechanism - Silva, Bruno (2015)
Dietary iron absorption regulation is one of the key steps for the maintenance of the body iron homeostasis. HFE gene expression undergoes a complex post-transcriptional alternative splicing mechanism through which two alternative transcripts are originated and translated to a soluble HFE protein isoform (sHFE). The first purpose of this study was to determine if sHFE transcript levels respond to different iron conditions in duodenal and macrophage cell models. In addition, we aimed to determine the functional effect of the sHFE protein on the expression of iron metabolism-related genes in a duodenal cell model as well as, in vivo, in duodenumbiopsy samples. Levels of sHFE transcripts were measured in HuTu-80, Caco-2, HT-29 and activated THP1 cells, after holo-Tf stimulus, and in total RNA from duodenum biopsies of functional dyspepsia patients. Also, the expression of several iron metabolism-related genes was determined after endogenous and exogenous overexpression of sHFE protein in a duodenal cell model. sHFE endocytosis mechanism was studied using endocytosis inhibitors. Our results showed that sHFE transcript expression was up-regulated after holo-Tf stimuli. Hephaestin and duodenal cytochrome b expressions were down-regulated by both endogenous HFE and sHFE proteins in a duodenal cell model. Exogenous sHFE was able to down-regulate hephaestin mRNA levels by a clathrin-independent, dynamin-mediated, and RhoA-regulated endocytosis mechanism. Moreover, HEPH levels negatively correlated with sHFE levels in the duodenum of functional dyspepsia patients. Thus, sHFE seems to be an important iron metabolism regulator playing a role in the control of dietary iron absorption in the duodenum.